Analisis Peran dan Dampak Social Enterprise di Kota Tasikmalaya - Rachmani, Nizza Nadya; Nurfitriya, Mira; Agisny, A; Hani, Salmia; Setiawati, Novianti Amalia (SAFE-Network, 2023)
This research proposed a framework to identify the impact of social enterprise on local communities in Tasikmalaya. Research on the impact of social enterprise on society in dealing with poverty problems, has been carried out in different locations, but no one has researched the impact of social enterprise in the Tasikmalaya area. Therefore, it is necessary to research the impact of the existence of a social enterprise on the surrounding community and in dealing with social problems that occur in the area around the existence of the social enterprise. This research used qualitative methods by collecting data through observation and in-depth interviews with social enterprise actors and the surrounding community. The results of the research showed that there are four roles of social enterprise that can be identified in Tasikmalaya, and five impacts of social enterprise on the recipient communities are found. In general, social enterprises have a positive impact on society in economic, social and environmental aspects.